Sorts of Business Students' motivation in learning English - Titien Indrianti; Bambang Suryanto; Eny Widiyowati (Politeknik Negeri Bali, 2022)
Motivation has been a crucial part in language learning, including English since it contributes one’s success in learning the target language. Meanwhile, sorts of motivation vary. Therefore, the present study is intended to investigate the sorts of motivation in learning English as possessed by the students of Business Administration at State Polytechnic of Malang. The questionnaires were distributed to the students of two different study programs: Office Administration and Marketing Management. The data were then put in the table of distribution. It is confirmed that the students are highly motivated in learning English. Their intrinsic and integrative motivation surpass the other sorts of motivation. It indicates that the students have their internal drive to like and learn English. However, the external factors, like teacher, materials, for study, and career have become additional contributing factors toward their high motivation. Therefore, it is advisable that a careful program of English learning is provided to those highly-motivated students. Besides, a supporting English atmosphere and facilities are also essential. Last but not least, the successful English learning requires a better commitment among the members of the Department. Keywords: intrinsic reward-oriented motivation, extrinsic reward-oriented motivation, instrumental socially-oriented motivation, integrative socially-oriented motivation